MENGUATKAN PERAN GURU SD DI ERA KECERDASAN BUATAN : PEDAGOGIK KRITIS BERBASIS KEARIFAN LOKAL PUPUH SUNDA - Loviana, Tira; Dini Novianti; Windi Nur Oktaviani; Jenuri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The exponential growth of artificial intelligence has sparked crucial debates regarding the potential weakening of teachers' roles in educating students. This article argues that the role of teachers as humanistic educators cannot possibly be replaced by technology. By using a systematic literature review method, this article proposes strengthening the role of teachers elementary school through a critical pedagogy framework harmonized with the local wisdom of Pupuh Sunda. Critical pedagogy rooted in Freire's thinking provides a foundation for developing students' critical awareness of technology. Meanwhile, the teaching of Pupuh Sunda offers a treasure trove of noble values such as patience, empathy, and responsibility that are relevant to character education. The synthesis between critical pedagogy and Pupuh Sunda produces transformative teaching strategies, where teachers not only transfer knowledge but also facilitate critical reflection, build character, and cultivate cultural sensitivity. In conclusion, the era of artificial intelligence actually serves as a momentum for teachers to reaffirm their urgency as agents of humanization that cannot be replaced by any sophisticated algorithm.